Religion and labor market performance: is it what you believe or how much? - Öhlmann, Philipp (Religions, 2021)
A growing corpus of literature has explored the influence of religion on economic attitudes and behavior. The present paper investigates the effect of religion on labor market performance using a novel approach to control for the endogeneity of religion. It proposes contingency experience, individual experiences of existential insecurity, as an instrumental variable of a person’s religiosity. The empirical analysis uses data from a household survey in South Africa specifically designed for this study. The econometric approach is the estimation of instrumental variable ordered probit and linear probability models. Using the Centrality of Religiosity Scale (CRS), the analysis differentiates between effects of individual religious intensity and of religious affiliation. The findings show that individual religiosity, measured in the CRS, has a robust and positive effect on labor market performance. Religious affiliation does not seem to affect labor market performance. The positive effect on religiosity is documented in a set of ordered and binary outcome models across different indicators of labor market performance. The study concludes that the intensity of belief exerts an influence on labor market attitudes and outcomes, while affiliation in religious communities (indicating different content of belief) does not seem to make a difference.